Strategi Gastrodiplomasi Thailand dalam Sektor Pariwisata untuk Meningkatkan Kunjungan Wisatawan Mancanegara (Studi Kasus Gastrodiplomasi Thailand di Indonesia) - Jannatun Naim; Alfian Hidayat; Sirwan Yazid Bustami (The Department of International Relations Universitas Mataram, 2022)
The potential of cuisine as a part of every country’s culture, if we can seriously manage it properly, could contribute to several sectors of the country. Utilizing culinary is also part of national branding. This strategy was implemented by Thailand to form a positive image of the country. The implementation of utilizing culinary potential is called gastrodiplomacy or culinary diplomacy. This research has two purposes: to understand Thailand’s gastrodiplomacy program and the strategies taken to increase foreign tourist arrivals. This research uses a qualitative and descriptive approach and uses data from secondary sources. Furthermore, in practice, this research will be expected to be able to provide insights for readers and writers about how Thailand’s strategy through gastro diplomacy is carried out in increasing foreign tourist arrivals